Identifikasi Bahaya dengan Metode Hirarc Pada Kegiatan Hose Connection di Departement Jetty PT XYZ - Raihan Firmansyah; Yanuar Pandu Negoro; Hidayat Hidayat (Jurnal Serambi Engineering, 2023)
The Jetty Department is a department that supports production because it is the initial point of entry for raw materials for production activities which are brought by a fleet of ships from outside Java. In the Jetty Department there are many types of work that have a risk of danger, one of the jobs that will be identified as dangerous in this research is hose connection activities. This research was carried out to identify hazards or dangers that could occur to workers, assess the risks, and finally be able to control the risk of danger using the HIRARC (Hazard Identification, Risk Assessment, and Risk Control) method. The research results show that in the risk assessment, there are 4 Low Risks, which means the risk is still acceptable, 5 Moderate Risks, which means the risk is still acceptable but needs additional risk control, and 3 high risks, which means the risk is not accepted, the risk needs to be reduced immediately. The proposed risk is to always use PPE that is appropriate to the job, and use work support tools such as supports and heavy forklifts. As well as always focusing on carrying out work, you must always be alert and responsive to areas or work environments that can pose risks and have good mutual coordination or communication between related workers.